2019
DOI: 10.1097/ijg.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intraocular Pressure and Angle Status After Phacoemulsification in Primary Angle Closure Hypertension

Abstract: Purpose: To study the change in intraocular pressure (IOP) and angle status after phacoemulsification in a cohort of primary angle closure hypertension (PACHT) patients. Setting: Tertiary Eye Care, India. Design: Prospective interventional case-series. Methods: Case-series of 18 eyes of 18 patients. Preoperative biometry including axial length, anterior chamber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Our study showed improvement in postoperative visual acuity, and there was no signi cant difference in uncorrected distance visual acuity between the MIOL and mIOL groups. This same nding was previously reported from a study that compared MIOLs and mIOLs in nonglaucomatous eyes [13]. The present study found the postoperative CS to be highest at 3 CPD in the mIOL group, and at 6 CPD in the MIOL group.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study showed improvement in postoperative visual acuity, and there was no signi cant difference in uncorrected distance visual acuity between the MIOL and mIOL groups. This same nding was previously reported from a study that compared MIOLs and mIOLs in nonglaucomatous eyes [13]. The present study found the postoperative CS to be highest at 3 CPD in the mIOL group, and at 6 CPD in the MIOL group.…”
Section: Discussionsupporting
confidence: 91%
“…Improvement in glaucoma control after cataract surgery was reported, and the observed improvement was found to be more pronounced in angle-closure than in open-angle glaucoma [7,13]. Our study demonstrates the positive effect of cataract surgery in PAC/PACG, including deepening of the ACD and IOP reduction.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations